(Hetero)aryl‐SVI Fluorides: Synthetic Development and Opportunities. (27th April 2022) - Magre, Marc; Ni, Shengyang; Cornella, Josep
Abstract: (Hetero)arylsulfur compounds where the S atom is in the oxidation state VI represent a large percentage of the molecular functionalities present in organic chemistry. More specifically, (hetero)aryl‐S VI fluorides have recently received enormous attention because of their potential as chemical biology probes, as a result of their reactivity in a simple, modular, and efficient manner. Whereas the synthesis and application of the level 1 fluorination at S VI atoms (sulfonyl and sulfonimidoyl fluorides) have been widely studied and reviewed, the synthetic strategies towards higher levels of fluorination (levels 2 to 5) are somewhat more limited. This Minireview evaluates and summarizes the progress in the synthesis of highly fluorinated aryl‐S VI compounds at all levels, discussing synthetic strategies, reactivity, the advantages and disadvantages of the synthetic procedures, the proposed mechanisms, and the potential upcoming opportunities. Abstract : The number of methods that exploit the synthesis of (hetero)arylsulfur(VI) fluorides is steadily growing due to their potential in organic synthesis. This Minireview covers the synthesis of arylsulfur(VI) fluorides from levels 2 to 5 of fluorination, the substrate scope, mechanisms, and the further applicability of these fluorinated compounds.